2019
DOI: 10.4067/s0718-58392019000400565
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome assembly and expression analysis in Colletotrichum gloeosporioides -tolerant Rubus glaucus Benth.

Abstract: Andean blackberry (Rubus glaucus Benth.) is an important crop of the Andean region affected by Colletotrichum gloeosporioides. In Colombia, tolerant plant material has been detected, but it has not been completely characterized. The objective of this research was oriented to analyze de novo transcriptome assembly of R. glaucus, and the comparison of the assembly with different reference genomes to further complete differential expression analysis of R. glaucus tolerant to C. gloespoiorides attack. To achieve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(65 reference statements)
1
1
0
Order By: Relevance
“…This work confirms that virus discovery can be accelerated through the analysis and reinterpretation of public sequencing data (Maree, 2018;Villamor et al, 2019;Buddenhagen et al, 2021 andGhosh et al, 2022). In our case, datasets were derived from studies focused on basic genome and transcriptome characterization of Rubus species (Hyun et al, 2014;Garcia-Seco et al, 2015;Sharma et al, 2019;Chen et al, 2018;Yan et al, 2020;Li et al, 2021;Yang et al, 2021;Wu et al, 2022a,b;Brůna et al, 2023 andMcGavin et al, 2023); analysis of the transcriptional response to upon infection with pathogens (Arias et al, 2019 andGonzález et al, 2020); and the validation of virus detection pipelines (Baizan-Edge et al, 2019;Gauthier et al, 2022 andMcGavin et al, 2023). Our most interesting results involved the identification of a putative new member of the genus Brambyvirus in data from a transcriptomic analysis of flavonoid biosynthesis (Li et al, 2021); and a putative new member of the family Virgaviridae in data used to test a plant virus detection workflow (Baizan-Edge et al, 2019).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This work confirms that virus discovery can be accelerated through the analysis and reinterpretation of public sequencing data (Maree, 2018;Villamor et al, 2019;Buddenhagen et al, 2021 andGhosh et al, 2022). In our case, datasets were derived from studies focused on basic genome and transcriptome characterization of Rubus species (Hyun et al, 2014;Garcia-Seco et al, 2015;Sharma et al, 2019;Chen et al, 2018;Yan et al, 2020;Li et al, 2021;Yang et al, 2021;Wu et al, 2022a,b;Brůna et al, 2023 andMcGavin et al, 2023); analysis of the transcriptional response to upon infection with pathogens (Arias et al, 2019 andGonzález et al, 2020); and the validation of virus detection pipelines (Baizan-Edge et al, 2019;Gauthier et al, 2022 andMcGavin et al, 2023). Our most interesting results involved the identification of a putative new member of the genus Brambyvirus in data from a transcriptomic analysis of flavonoid biosynthesis (Li et al, 2021); and a putative new member of the family Virgaviridae in data used to test a plant virus detection workflow (Baizan-Edge et al, 2019).…”
Section: Discussionsupporting
confidence: 78%
“…Given the lack of financial resources for basic research in developing countries, we have shown that data mining can become a powerful tool to provide additional epidemiological insights for crops of interests. In our case, a single RNA sequencing study from Colombia, generated to investigate the response of infection with the fungus Colletotrichum gloeosporioides (Arias et al, 2019), provided a valuable glimpse of viruses circulating in Colombia that might represent a potential threat in the productivity of R. glaucus such as: RBDV, PYV, RIV2-1, and RIV-2.…”
Section: Discussionmentioning
confidence: 99%